A study of the impact of the ARCH model of parenting on the psychosocial well-being of children and their parents during the COVID-19 pandemic - Kalawadia, Dhruv; Ramkrishna, Suradharadhika; Verma, Bela; Dalwai, Samir; Garg, Manish (Indian Journal of Child Health, 2022)
Introduction: The COVID-19 pandemic and its associated lockdowns have affected the development of children negatively. The ARCH model is a parent-administered, home-based, psychological intervention model to improve the psychosocial well-being of children and their families. The model acts as a set of guidelines and a list of activity modules for parent-child interactions that will promote and enhance the child’s social skills and psychological health. Objective: The objective of the study was to study the effectiveness of a novel innovative psychological model and parenting strategy for promoting the psychosocial well-being of children. Materials and Methods: This is an open prospective single-arm study in a tertiary care hospital with pre-and post-intervention design. Patients aged 3–18 years visiting the outpatient department, admitted to the pediatric ward as well as their parents, and siblings, were enrolled in the study. Data were collected by self-reported questionnaires. The intervention was administered and 1–2 months later we checked for any changes in the psychosocial well-being scores. Results: Fifty participants were enrolled and eight were lost to follow-up. Statistical analysis showed an insignificant difference in the Ryff psychosocial well-being pre-intervention score (208.5±15.1) and post-intervention scores (208.4±14.8) (p=0.847) for parents. KIDSCREEN questionnaire score showed a significant improvement in “social service and peers” subcategory, between pre-intervention score (128.83±17.18) and post-intervention score (131.29±16.60) with a Z score=2.09 (p<0.05). KIDSCREEN questionnaire score also showed improvement in overall score in pre-intervention score (578.64±440.39) and post-intervention score (584.40±444.19) with a Z score=1.66 (p<0.05). Conclusion: Our study found that while the intervention did not have a major impact on the psychosocial well-being of the parents, there was a significant difference effected on the psychosocial well-being of the children.